Understanding the Dynamics of Defense Industry Cooperation within the Framework of the Indonesia Australia Defense Security Dialogue: Memahami Dinamika Kerjasama Industri Pertahanan dalam Kerangka Indonesia Australia Defence Security Dialogue (Journal of Political Issues, 2023)
The defense industry has become one of the important agendas and has become a concern, starting with the United Indonesia Cabinet I under President Susilo Bambang Yudhoyono and making it a development priority and providing great opportunities for the involvement of the private sector in defense industry activities, one of which is through the cooperation agenda established by Indonesia and Australia are in a dialogue agenda Indonesia - Australia Defense Security Dialogue (IADSD) Therefore this research aims to find problems in order to achieve the research objectives, using the concept of the Military Industrial Complex (MIC) and also the Iron Triangle theory in which there are three main actors who play a role in optimization and the linkages between the relationship lines of the actors involved. In enhancing the Defense Industry in Indonesia, it is certainly very complex, but in this case there are also key actors referring to the political economy relationship that occurs between legislators, the national armed forces, and the weapons industry. These relationships are related to political contributions, political approval of military spending, lobbying to support the bureaucracy, and industry. The three bodies, which at present are more commonly referred to as congress / parliament, defense ministry, and defense industry, are then referred to as the iron triangle of defense. In which this involvement is narrowed back to the focus of the land dimension in this implementation, PT. Pindad and also the end-user of the Indonesian Armed Forces (TNI AD) in order to reduce dependence on foreign products and further increase the independence of the national defense industry.
Keywords: Australia; Defense Industry; Indonesia; Lombok Treaty